2020
DOI: 10.24141/2/4/1/1
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with the Work of Nurses in Primary Health Care

Abstract: Introduction. Patient satisfaction with provided health care is an important indicator of health care quality. Research on patient satisfaction has been very frequent in recent years. Aim. A prospective, cross-sectional study was conducted at the Health Centre of the Ministry of the Interior of the Republic of Croatia between April and June 2019. The aim of this study was to examine the satisfaction of patients with the work of nurses in primary health care. Methods. A standardized Nursing Practitioner Sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
1
2
Order By: Relevance
“…Additionally, in the current study, more than 50% of patients were dissatisfied with the nursing staff, contrary to the study conducted by Franjo et al. (2020), which showed that patients are satisfied with nurse work. More than 60% of the participants responded that they were satisfied with the management of the PHC center and receptionists.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Additionally, in the current study, more than 50% of patients were dissatisfied with the nursing staff, contrary to the study conducted by Franjo et al. (2020), which showed that patients are satisfied with nurse work. More than 60% of the participants responded that they were satisfied with the management of the PHC center and receptionists.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, another study conducted in Brazil found that 90% would recommend PHC centers to their relatives due to the doctors' gentle treatment (Cantalino et al, 2021). Additionally, in the current study, more than 50% of patients were dissatisfied with the nursing staff, contrary to the study conducted by Franjo et al (2020), which showed that patients are satisfied with nurse work. More than 60% of the participants responded that they were satisfied with the management of the PHC center and receptionists.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation